Clinical trial going on for 10 years - how is it possible? - Mimica, Ninoslav (Array, 2009)
Controlled clinical trials of very long duration (more than ten years) are very rare in psychiatry, due to numerous reasons, although it is obvious that these trials can make a substantial contribution to our knowledge regarding maintenance use of particular antipsychotic drugs. Due to the fact that some novel antipsychotics are not yet registered in Croatia and in some other European countries, that is, not available on the market, we still have patients who participate in an open-label extension of a clinical study, taking medication continually under supervision, for more than ten years